Towards a community of practice on climate security and environmental peacebuilding in Mindanao - Medina, Leonardo; Savelli, Adam; Jaquet, Stéphanie; Hellin, Jon; Torres, Mark Anthony; Arcede, Jayrold; Taiwo, Ibukun (2023)
Between the 24th and 26th of October, CGIAR’s Climate Resilience Initiative (ClimBeR) ran a climate security and environmental peacebuilding workshop in Butuan, Mindanao: Towards a community of practice for Climate Security and Environmental Peacebuilding in Mindanao. The workshop was organized jointly by Mindanao State University – Iligan Institute of Technology, Caraga State University, Agusan Del Sur State University College of Agriculture and Technology, ECOWEB, CGIAR’s Initiative on Fragility, Conflict, and Migration (FCM), and CGIAR FOCUS Climate Security, and benefited from the participation of government institutions, international organizations, NGOs, and universities.